Examining the relationship between hoteliers’ review site use intensity and hotel characteristics - Moroccan Hotels - Ait-Bakrim, Abderrahman (2020)
Due to rapid development and consumer adoption of technology, the hospitality industry has dramatically increased online-based user-generated reviews for a variety of services, such as those found in eWOM communities (e.g., TripAdvisor). Few studies have tested-among eWOM communities-the correlation between hoteliers' review site use intensity and hotel characteristics. The purpose of this paper is to examine the predictors of TripAdvisor use intensity, as perceived by Moroccan hoteliers. After the literature review on user-generated content, a quantitative study based on a structured questionnaire survey was developed, and correlation analyses were conducted to empirically validate the relationship between hotel characteristics and the use of TripAdvisor among a population of 48 hotel managers. The results showed that all variables studied commitment, competence, hotel size (number of beds), hotel category, and type of ownership were positively related to the intensity of use of review sites. This study deepens hotel practitioners' understanding of the importance of user-generated content and offers suggestions on how to improve eWOM advocacy. Moreover, this paper contributes to the recent and still scanty research line on eWOM from the hoteliers' perspective. The novelty lies in the positive relationships between hotel features (commitment, competence, hotel size, hotel category, and type of ownership) and user-generated review sites (TripAdvisor). It extends current literature and provides practitioners with some guidance on user-generated content and hotel characteristics.